The Indonesian Version of Sayles Internalized HIV Stigma Scale: Preliminary Test of Reliability - Nyoman Agus Jagat Raya; Ni Made Sekar Sari (Babali Nursing Research, 2023)
The needs for an Indonesian version of a tool to measure internalized HIV stigma are identified. This study aims to evaluate the reliability of the Indonesian version of Sayles Internalized HIV Stigma Scale and the correlation of each subscale. A cross-sectional preliminary study involving purposively sampled 20 persons infected with HIV in Bali, Indonesia was conducted. The internal consistency reliability was examined through Cronbach’s α and item-total correlation. Meanwhile, the correlation of each subscale was examined by using Spearman’s Rank correlation coefficient. The results showed a Cronbach’s α of 0.924 and the item-total correlation range from 0.151 to 0.837. Significant positive correlation between overall scale and each subscale were confirmed. These findings indicated acceptable reliability of the Indonesian version of Sayles Internalized HIV Stigma Scale and the possibility of its use as an alternative to assess the internalized HIV stigma in Indonesia.